The electrochemical study of graphene - Nurizzuddin , Ahmad Hussin (2012)
Synthesis of graphene from graphite was produced by electrolytic exfoliation using poly (sodium-4-styreflesUlfOflate) as an effective electrolyte. Two graphite rods were placed in an electrolysis cell filled with the electrolyte. As the result, we will obtain dry graphene powders and the dried sediment. Advantage of graphene mobility of charge carriers, unique transport performance, high mechanical strength, and extremely high thermal conductivity. It's suitable for many technological applications scanning and transmission electron microscopy and atomic force microscopy confirmed the existence of monolayer graphene sheets and stacks containing a few graphene sheets. Graphene powder will be characterized by FTIR, BET, and CV. Why we use graphene? It's because graphene has high electrical conductivity gives these materials consistently good performance over a wide range of voltage scan rates. Graphene has the potential to enable major advances in energy storage has high